Aggregation behavior and non‐covalent functionalization of borofullerenes B28, B38, and B40: A density functional theory investigation. Issue 14 (4th March 2019) - Yang, Le; Li, Ying; Hao, Debo; Li, Lanlan; Peng, Huifen; Jin, Peng
Abstract: Fullerene‐like boron clusters (borofullerenes) are rising stars in the field of cluster chemistry. In this work, density functional theory calculations revealed that the recently reported small borofullerenes Bn (n = 28, 38, and 40) are all highly reactive and tend to form dimers and even trimers spontaneously. In addition, the non‐covalent modification of these borofullerenes by various cycloparaphenylene nanorings can form stable host‐guest systems with substantial intermolecular charge transfer at both ground and excited states. Our results demonstrate that the borofullerenes are versatile platform for exohedral functionalization, and are very promising candidates for the design of novel nanomaterials with desirable properties. Abstract : Density functional theory calculations reveal that a series of small borofullerenes all tend to form dimers and even trimers with rather low energy barriers. For the first time theoretical investigations show that non‐covalent functionalization by different cycloparaphenylene rings helps the protection and isolation these boron cages, but also may lead to stable host‐guest supramolecules with novel charge transfer properties.